Bacteria existing in pre-pollinated styles (silks) can defend the exposed male gamete fertilization channel of maize against an environmental Fusarium pathogen - Shrestha, Anuja; Limay-Rios, Victor; Brettingham, Dylan J. L.; Raizada, Manish N. (Frontiers in Plant Science, 2023)
In flowering plants, fertilization requires exposing maternal style channels to the external environment to capture pollen and transmit its resident sperm nuclei to eggs. This results in progeny seed. However, environmental fungal pathogens invade developing seeds through the style. We hypothesized that prior to environmental exposure, style tissue already possesses bacteria that can protect styles and seed from such pathogens. We further hypothesized that farmers have been inadvertently selecting immature styles over many generations to have such bacteria. We tested these hypotheses in maize, a wind-pollinated crop, which has unusually long styles (silks) that are invaded by the economically-important fungal pathogen Fusarium graminearum (Fg). Here, unpollinated silk-associated bacteria were cultured from a wild teosinte ancestor of maize and diverse maize landraces selected by indigenous farmers across the Americas, grown in a common Canadian field for one season. The bacteria were taxonomically classified using 16S rRNA sequencing. In total, 201 bacteria were cultured, spanning 29 genera, 63 species, and 62 unique OTUs, dominated by Pseudomonas, Pantoea and Microbacterium. These bacteria were tested for their ability to suppress Fg in vitro which identified 10 strains belonging to 6 species: Rouxiella badensis, Pantoea ananatis, Pantoea dispersa, Pseudomonas koreensis, Rahnella aquatilis, and Ewingella americana. Two anti-Fg strains were sprayed onto silks before/after Fg inoculation, resulting in ≤90% reductions in disease (Gibberella ear rot) and 70-100% reductions in associated mycotoxins (deoxynivalenol and zearalenone) in progeny seeds. These strains also protected progeny seeds post-harvest. Confocal fluorescent imaging showed that one silk bacterium (Rouxiella AS112) colonized susceptible entry points of Fg on living silks including stigmatic trichomes, wounds, and epidermal surfaces where they formed thick biofilms. Post-infection, AS112 was associated with masses of dead Fg hyphae. These results suggest that the maize style (silk) is endowed with potent bacteria from the mother plant to protect itself and progeny from Fusarium. The evidence suggests this trait may have been selected by specific indigenous peoples, though this interpretation requires further study.